Mexican consensus about surgical treatment in early-stage cervicouterine cancer - Nájera-Muñoz, Cindy A.; Hernández-Romero, Raúl; Isla-Ortiz, David; Salcedo-Hernández, Rosa A. (Frontiers in Oncology, 2024)
Introduction. Cervical cancer is a public health problem in our country and worldwide. Less than 25% of cases are diagnosed in the early stages, where survival is more remarkable than 90% at five years. Here, we review surgical treatment in the early stages of cervical cancer. Methodology. A literature review was carried out in the MEDLINE database. The search was mainly limited to the English language, with priority given to systematic reviews with or without meta-analysis and randomized studies. However, only retrospective or observational evidence was found for some topics. Results. The standard treatment for early-stage cervical cancer is hysterectomy, and its radical nature will depend on the tumor size, lymphovascular permeation, and tumor-specific prognostic factors. Furthermore, the type of surgery (hysterectomy or trachelectomy) will rely on the patient's desire to preserve fertility. Nodal evaluation is indicated as part of the treatment from stage IAI with PLV. However, the sentinel lymph node is more relevant in the treatment. The incidental finding of cervical cancer after a hysterectomy requires a multidisciplinary evaluation to determine the therapeutic approach. Less radical surgery has been described as oncologically safe in low-risk groups. Conclusion. Surgical treatment in its early stages has evolved in recent decades, making it more individualized and seeking less morbidity in patients without compromising their survival.